On PTAs and bilateral trade: Is GVC trade sensitive to the breadth of trade policy cooperation? - Michele Delera; Neil Foster-McGregor (Economies, 2020)
We study the relationship between the scope of trade policy cooperation and bilateral trade flows with a particular focus on global value chain (GVC) trade using data on the core and non-core provisions included in preferential trade agreements (PTAs). We find that broader PTAs have a larger impact on trade flows involving intermediates relative to flows involving all products, suggesting that GVC trade is particularly sensitive to the scope of trade policy cooperation. We also investigate different dimensions of heterogeneity in PTAs. We find that core provisions tend to drive the effect of PTAs on the level of GVC trade and that PTAs are particularly effective in raising the level of GVC trade between developing economies. We explore these issues using a sample of 189 countries over the period 1990-2015, with data obtained from the latest release of the EORA multi-regional input-output tables and UN-COMTRADE data.
Keywords: F10; F14; F15; F63; 330; PTAs; PTA breadth; horizontal depth; GVCs; structural gravity model